¿Reformar sin los docentes?: identidad profesional, resistencia y mediación a la reforma de la educación secundaria en Perú (Revista Peruana de Investigación Educativa, 2021)
Can an educational reform ignore the agency and mediation of teachers? How does it feel for teachers’professionalism to be assumed as executors of programs designed by external policy makers? Under these premises, this article aims to explore and analyze the responses and ideas about professionalism and the mediation and resistance of secondary school teachers towards the standardized sessions policy designed by MINEDU in the context of the implementation of the Full School Day-JEC. The case provides a textbook example of a hierarchical reform based on neoliberal single-design and accountability approaches to fidelity of implementation implemented in a particular context of harsh working conditions and deprofessionalization of secondary school teachers. This article is based on an exploratory research product of in-depth field work in two rural secondary schools. The findings show that in the context of the JEC reform, the professional teaching role is reconfigured in all its dimensions: professional judgment, exercise of identity and self-assessment, and political positions. Teachers react to this challenge in their professional agency by constructing contradictory responses to reform and actions of resistance to implementation driven by competitive imperatives in their discourse. In addition, the findings show that in the context of rural JEC schools, given the conditions of high inequality and challenge, the rejection of the reform and its weaknesses are used to reinforce the use of negative professional strategies such as absenteeism, alienation and mistrust towards those proposed by MINEDU.